2015
DOI: 10.1002/jcc.24034
|View full text |Cite
|
Sign up to set email alerts
|

Computational assessment of electron density in metallo-organic nickel pincer complexes for formation of PC bonds

Abstract: Hydrophosphination is an atomically efficient method for introducing new carbon-phosphorous bonds in organic synthesis. New late-transition metal catalytic complexes are proposed to facilitate this process. These nickel-based complexes are analyzed using semiempirical (SE), Hartree-Fock (H-F), and density functional theory (DFT) models. H-F proves to be ineffective, while the SE approach has limited, qualitative use. DFT shows electron density at the metal center suitable for catalyzing bond formation in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…Togni and co‐workers identified a Lewis acidic interaction between a PPP–Ni II pincer complex and the electron‐deficient olefin substrate . On the other hand, purely theoretical investigations in the absence of experimental support by Downey and co‐workers led to an alternative mechanism in which the active Ni–PPh 2 catalytic species was generated by displacing the Ni−Cl bond of the POCOP Ni II –Cl pre‐catalyst . Notably, direct participation of the Ni II center was involved in both proposed catalytic cycles and the active catalytic species were only generated in situ under reaction conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Togni and co‐workers identified a Lewis acidic interaction between a PPP–Ni II pincer complex and the electron‐deficient olefin substrate . On the other hand, purely theoretical investigations in the absence of experimental support by Downey and co‐workers led to an alternative mechanism in which the active Ni–PPh 2 catalytic species was generated by displacing the Ni−Cl bond of the POCOP Ni II –Cl pre‐catalyst . Notably, direct participation of the Ni II center was involved in both proposed catalytic cycles and the active catalytic species were only generated in situ under reaction conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work using nickel‐based complexes confirmed that these complexes are relatively insensitive to solvent dielectric constant and to the chemical character of the monodentate ligand in terms of electron distribution and molecular orbital energies. It also showed that density functional theory (DFT) was the most accurate modeling approach for modeling this family of complexes . It did not, however, include analysis of the available functionals for use within DFT, instead considering only DFT‐B3LYP.…”
Section: Introductionmentioning
confidence: 93%
“…Because the precursor complexes are of interest for rapid generation of catalysts via ligand exchange, a key consideration is the presence of energetically accessible electron density centered on the metal cation. [15] Alternatively, the incoming phosphine ligand may bond to the metal center by donating electrons to the precursor complex lowest unoccupied molecular orbital (LUMO), in the case that the LUMO offers significant involvement at the metal center. Therefore, for each precursor complex, the highest unoccupied molecular orbital (HOMO) and LUMO were characterized ( Table 4) in terms of electron density at the center of the complex.…”
Section: Electron Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14,100] A computational assessment of electron density in a nickel pincer complex (Figure 57) with respect to the formation of P-C bonds was performed by Downey and coworkers. [101] The DFT analysis depicted electron density at metal centers suitable for catalyzing bond formation in a proposed, reductive hydrophosphination mechanism. Pincer complexes were shown to be insensitive to solvent dielectric constants through the orbital energies and consequently the HOMO-LUMO gap.…”
Section: Beletskayamentioning
confidence: 99%